Exploring influences of consumer socialization agents on branded apparel purchase among urban Malaysian tweens - Teo, Carol Boon Chui; Md. Sidin, Samsinar; Mohamad Nor, Mohd Izzudin (Universiti Putra Malaysia Press, 2013)
Tween consumers today interact with brands, television media and friends as their main agents of socialization. These agents have impacts on their consumption patterns. In the Malaysian market, the tween segment has emerged and also taken the retail trade by storm. Tweens are now able to influence their parents’ purchasing decisions and this has changed the spending behaviour of their family. This paper seeks to examine consumer socialization sources for tweens and how these socialization agents can influence their preference for branded apparels. Data was collected using a structured survey questionnaire to elicit responses on the purchase preferences of branded apparels. The respondents comprised of 150 urban tweens between the ages of 8 to 12 years. Findings revealed that urban tweens had relatively high awareness on brand names and strong purchase preferences for branded apparels. Peer, parental and advertisement influences, combined with their obsession for television media, have significantly affected their purchase of branded apparels. Arguably, parental selective power still has some exertion on tween's purchase decisions although the influence is declining. Parents and tweens often wear apparels of the same brands. The findings of this study have several implications for marketers, consumers, and family policy makers.